Assessment of Autotronics Servicing Skill Needs among Roadside Mechanics for the Use of Auto Scan Tools - Stephen Z. Kumazhege; Eric B. Enoch; Nasiru Sani Zakirai; Umar Abubakar Madabai (Journal of Novel Engineering Science and Technology, 2023)
This study examined the Autotronics Servicing Skills needs among Roadside Mechanics and Master Trainers using auto scan tools. Two research questions and two null hypotheses guided the study. The study was carried out in 9 local government areas of Kano State. The study population was 90 Road Side Mechanics, and Masters Trainers selected through a simple random sampling technique. The whole population was used for the study. A structured questionnaire validated by three experts from the Department of Technology Education, Modibbo Adama University, Yola and trial tested for internal consistency in the Ringim local government area of Jigawa State was used. The instrument yielded a reliability coefficient of 0.82. The instrument structured on 5 points Likert scale was used to elicit information on using the Onboard diagnostic (OBD2) and Launch code reader professional 123 (CRP123) for diagnosing vehicle systems faults. Data collected were analyzed using Microsoft Excel. Mean and standard deviation was used to answer the research questions. Z-test statistics were used to test the null hypotheses at a 0.05 significance level. The study found out that Roadside Mechanics need autotronics servicing skills in the use of OBD2 and CRP123 for diagnosing and fixing problems in the engine, transmission, airbag (supplemental restraint system SRS), anti-lock braking system (ABS), and emission-related systems. The study recommended that ASS acquisition centres should be established in Kano State by organizations like the Ministries of Labour, the National Directorate for Employment (NDE), the National Automotive Design and Development Council (NADDC), the National Board for Technical Education (NBTE) and so on to enable Roadside Mechanics and other people who wish to learn the skills to acquire the required training to meet up with the challenges ever increasing in the motor vehicle technology.